Genetic deficiency of glycogen synthase kinase-3beta corrects diabetes in mouse models of insulin resistance. - Katsuya Tanabe; Zhonghao Liu; Satish Patel; Bradley W Doble; Lin Li; Corentin Cras-Méneur; Sara C Martinez; Cris M Welling; Morris F White; Ernesto Bernal-Mizrachi; James R Woodgett; M Alan Permutt (PLoS Biology)
Despite treatment with agents that enhance beta-cell function and insulin action, reduction in beta-cell mass is relentless in patients with insulin resistance and type 2 diabetes mellitus. Insulin resistance is characterized by impaired signaling through the insulin/insulin receptor/insulin receptor substrate/PI-3K/Akt pathway, leading to elevation of negatively regulated substrates such as glycogen synthase kinase-3beta (Gsk-3beta). When elevated, this enzyme has antiproliferative and proapoptotic properties. In these studies, we designed experiments to determine the contribution of Gsk-3beta to regulation of beta-cell mass in two mouse models of insulin resistance. Mice lacking one allele of the insulin receptor (Ir+/-) exhibit insulin resistance and a doubling of beta-cell mass. Crossing these mice with those having haploinsufficiency for Gsk-3beta (Gsk-3beta+/-) reduced insulin resistance by augmenting whole-body glucose disposal, and significantly reduced beta-cell mass. In the second model, mice missing two alleles of the insulin receptor substrate 2 (Irs2-/-), like the Ir+/- mice, are insulin resistant, but develop profound beta-cell loss, resulting in early diabetes. We found that islets from these mice had a 4-fold elevation of Gsk-3beta activity associated with a marked reduction of beta-cell proliferation and increased apoptosis. Irs2-/- mice crossed with Gsk-3beta+/- mice preserved beta-cell mass by reversing the negative effects on proliferation and apoptosis, preventing onset of diabetes. Previous studies had shown that islets of Irs2-/- mice had increased cyclin-dependent kinase inhibitor p27(kip1) that was limiting for beta-cell replication, and reduced Pdx1 levels associated with increased cell death. Preservation of beta-cell mass in Gsk-3beta+/- Irs2-/- mice was accompanied by suppressed p27(kip1) levels and increased Pdx1 levels. To separate peripheral versus beta-cell-specific effects of reduction of Gsk3beta activity on preservation of beta-cell mass, mice homozygous for a floxed Gsk-3beta allele (Gsk-3(F/F)) were then crossed with rat insulin promoter-Cre (RIP-Cre) mice to produce beta-cell-specific knockout of Gsk-3beta (betaGsk-3beta-/-). Like Gsk-3beta+/- mice, betaGsk-3beta-/- mice also prevented the diabetes of the Irs2-/- mice. The results of these studies now define a new, negatively regulated substrate of the insulin signaling pathway specifically within beta-cells that when elevated, can impair replication and increase apoptosis, resulting in loss of beta-cells and diabetes. These results thus form the rationale for developing agents to inhibit this enzyme in obese insulin-resistant individuals to preserve beta-cells and prevent diabetes onset.